DAMPAK PERTUMBUHAN EKONOMI, INFLASI, DAN KURS TERHADAP FOREIGN DIRECT INVESTMENT (FDI) DI INDONESIA - Korneles Sangur; Lisye Magdalena Liur (Jurnal Cita Ekonomika, 2022)
ABSTRACT Research Method: Multiple regression model. The method of data collection carried out is the literature method. Results: The effect of GDP, inflation, and exchange rate, then obtained the value of f-count > f-table (16.24765> 3.01 ) with a significant value of 0.000025 < 0.05, the effect of GDP on FDI investment in Indonesia shows an insignificant value with a prob value of > of 0.05 (0.0647 > 0.05) and a t-count value < t-table ( 2,013 < 2,945), the effect of inflation on FDI investment in Indonesia shows a significant value with a prob value < of 0.05 (0.0005 < 0.05) and t-count value < t-table (3,517 > 2,945), the effect of the exchange rate value on FDI in Indonesia shows an insignificant value with a prob value > from 0.05 (0.0659 > 0.05) and and a t-count < t-table (2,016 < 2,945). Conclusion: Showing simultaneously independent variables affecting dependent variables is shown by the f-count value > F-table. Partially, the economic growth variable calculated using GDP in 2000-2019 is positive and has no significant effect on FDI investment in Indonesia; inflation as seen from inflation data for 2000-2019 has a positive and significant effect on FDI investment in Indonesia; the exchange rate seen from the middle rate from 2000-2019 is positive and has no significant effect on FDI investment in Indonesia. Keywords : Economic Growth, Investment, Exchange Rate, Inflation